Harnessing wave energy using a heaving plate - Ang, Daniel Jin Ming (2014)
Extant literature has shown various wave energy-harnessing methods that are being employed around the world to tap on this high potential renewable energy source. While many studies have explored the operability and efficiency of current existing harnessing methods, no research has been carried out to consider the possibility of employing a heaving plate mechanism to harness wave energy. Our research aimed to investigate whether the difference in spring constant will have an effect on the hydrodynamic performance of the heaving plate and as well as to identify the optimum plate submergence depth to harness incoming wave energy efficiently, while at the same time reducing the level of wave agitation from the seawall. By integrating wave energy converters with wave absorption capabilities can be a promising way to reduce cost and make wave energy utilization more competitive.